Modifikasi Permainan Boi-Boian Sebagai Upaya Meningkatkan Motivasi Belajar - Firman Syah, Donny; Lestari Suryaningsih; Mochamad Ridwan (Jurnal Keolahragaan JUARA, 2024)
This research was motivated by the feeling of boredom and lack of enthusiasm among several class VI students at SDN Jeruk I/469 Surabaya in participating in Physical Education, Sports and Health (PJOK) lessons. This research aims to obtain information and determine the impact of providing modifications to the boi-boian game on student learning motivation in PJOK learning. This research method uses classroom action research, with implementation over 2 cycles. Data collection uses observation sheets, questionnaires and documentation with quantitative descriptive analysis techniques. The research subjects were 25 students who were class VI B students. The research results in cycle I had an average of 89.61. Then, in cycle II the average was 93.87. The results of this data acquisition increased by 4%, it can be concluded that there was an increase in student learning motivation in PJOK learning by implementing modifications to the boi-boian game.